2021
DOI: 10.1111/maps.13743
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and geochemistry of lunar feldspathic meteorite Northwest Africa 11111: Insights into the lithology of the lunar farside highlands

Abstract: We performed a petrological, mineralogical, and geochemical study of the lunar feldspathic meteorite Northwest Africa (NWA) 11111. This meteorite contains several types of lithic clasts, including feldspathic clasts, mafic‐rich clasts, granulites, impact melt breccias, minor basaltic clasts, and highly evolved clasts cemented in a recrystallized fine grain matrix. Both mineral chemistry and geochemical characteristics indicate a lunar origin for NWA 11111. The bulk analysis suggests that NWA 11111 is a typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
(220 reference statements)
0
2
0
Order By: Relevance
“…4 The REE content in NWA 11111 is the lowest; whereas it is the highest in the typical KREEP basalt of Apollo 15. In addition, we compared the elemental compositions obtained in the present study with the ICP-OES/ICP-MS data reported by Fu et al 22 for NWA 11111 and Elardo et al 23 for NWA 4734, which are also listed in Table 2.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…4 The REE content in NWA 11111 is the lowest; whereas it is the highest in the typical KREEP basalt of Apollo 15. In addition, we compared the elemental compositions obtained in the present study with the ICP-OES/ICP-MS data reported by Fu et al 22 for NWA 11111 and Elardo et al 23 for NWA 4734, which are also listed in Table 2.…”
Section: Resultsmentioning
confidence: 94%
“…The data obtained for the two meteorites were compared with previous results obtained via ICP-MS and inductively coupled plasma-optical emission spectrometry (ICP-OES). 22,23…”
Section: Introductionmentioning
confidence: 99%